Intrinsic ultrasmall nanoscale silicon turns n-/p-type with SiO2/Si3N4-coating - König, Dirk; Hiller, Daniel; Wilck, Noël; Berghoff, Birger; Müller, Merlin; Thakur, Sangeeta; Di Santo, Giovanni; Petaccia, Luca; Mayer, Joachim; Smith, Sean; Knoch, Joachim (Beilstein Journal of Nanotechnology, 2018)
Impurity doping of ultrasmall nanoscale (usn) silicon (Si) currently used in ultralarge scale integration (ULSI) faces serious miniaturization challenges below the 14 nm technology node such as dopant out-diffusion and inactivation by clustering in Si-based field-effect transistors (FETs). Moreover, self-purification and massively increased ionization energy cause doping to fail for Si nano-crystals (NCs) showing quantum confinement. To introduce electron- (n-) or hole- (p-) type conductivity, usn-Si may not require doping, but an energy shift of electronic states with respect to the vacuum energy between different regions of usn-Si. We show in theory and experiment that usn-Si can experience a considerable energy offset of electronic states by embedding it in silicon dioxide (SiO2) or silicon nitride (Si3N4), whereby a few monolayers (MLs) of SiO2 or Si3N4 are enough to achieve these offsets. Our findings present an alternative to conventional impurity doping for ULSI, provide new opportunities for ultralow power electronics and open a whole new vista on the introduction of p- and n-type conductivity into usn-Si.
Keywords: energy offset; impurity doping alternative; ultrasmall nanoscale silicon crystals; wires and devices